1987
DOI: 10.1007/bf01412751
|View full text |Cite
|
Sign up to set email alerts
|

Binding of hexadecylammonium surfactants to water-soluble neutral polymers

Abstract: The binding of hexadecyltrimethylammonium bromide and hexadecyldimethyl-2-hydroxyethylammonium bromide to neutral polymers was measured by a potentiometric titration method using surfactant selective electrodes. Binding to poly(vinyl alcohol) was slightly cooperative, while that to poly(ethylene oxide) lacked the cooperativity. Poly(vinyl pyrrolidone) did not bind them at all. Binding affinity as estimated by a distribution coefficient of the cationic surfactants between the bulk and polymer phases is about 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…51 The second contribution derives from the fact that PVA is an amphiphilic polymer known to bind to the surface of regular cationic surfactant micelles in aqueous solution thereby stabilizing them. 52,53 According to Lewis et al, 17 the beads contain 96 wt% water when in equilibrium with pure water. By subtracting the weight fraction of AMPS (16 mM corresponds to 0.5 wt%), we found that the 100-300 mm fraction contained approximately 3.5 wt% PVA, corresponding to approximately 800-mM uncharged vinyl alcohol segments or approximately 50 segments per network charge.…”
Section: Discussionmentioning
confidence: 99%
“…51 The second contribution derives from the fact that PVA is an amphiphilic polymer known to bind to the surface of regular cationic surfactant micelles in aqueous solution thereby stabilizing them. 52,53 According to Lewis et al, 17 the beads contain 96 wt% water when in equilibrium with pure water. By subtracting the weight fraction of AMPS (16 mM corresponds to 0.5 wt%), we found that the 100-300 mm fraction contained approximately 3.5 wt% PVA, corresponding to approximately 800-mM uncharged vinyl alcohol segments or approximately 50 segments per network charge.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of electrode has been extensively used by Wyn-Jones et al 48,[54][55][56][57]138,[140][141][142][143][144][145][146][147][148] and by the groups of Shirahama and Hayakawa. 49,[149][150][151][152][153][154] From Table 1, one can see that the polymers are mainly focused on PVP, PEO, PVA, HEUR, CD, MC, NaPA, PAMPS, Chitosan, and triblock-polymers such as Pluronic F68 (EO 76 PO 29 EO 76 ) and F127 (EO 97 PO 69 EO 97 ). [53][54][55][56]74 Anionic surfactants include sodium dodecyl sulfate (SDS), sodium tetradecyl sulfate (STS), etc.…”
Section: Interaction Between Polymers and Ionic Surfactantsmentioning
confidence: 99%
“…Particularly, the three-stage model [17] suggested by Biggs gained wide acceptance, in which the viscosity changes and the molecular configuration of the mixed systems can be divided into three stages with the increase of surfactant concentration. Many reports [18][19][20][21][22] showed that the interactions between HMP and surfactants might be also controlled by such factors as pH of the solutions, salts and hydrogen bounds between them, in addition to the properties of HMP and surfactants. The information of all these influences can be reflected from the conformations of the mixed system.…”
Section: Introductionmentioning
confidence: 99%